The harvestmen fauna (Arachnida: Opiliones) of the Katunsky Biosphere Reserve and adjacent territories (South Siberia, Russia), with a description of a new species of Sabacon (Sabaconidae) and notes on Sabacon sergeidedicatum Martens, 1989 - Trilikauskas, Laimonas A.; Azarkina, Galina N. (Zootaxa, 2021)
An annotated list of harvestmen species (six species in two families) of the Katunsky Biosphere Reserve and adjacent territories in the Altai Republic, Russia is provided. A new species, Sabacon zateevi sp. nov. (♂ ♀ from the Altai Mountains, Russia), is described. Liropilio stukanovi Gritsenko, 1979 is recorded from Russia for the first time, and appearance and diagnostic features of its male are described. The appearance of a living specimen of the female of Homolophus nordenskioeldi (C.L. Koch, 1879) is also provided. For all the studied species, biotope preferences and distribution are discussed. Additional information on morphology and distribution of Sabacon sergeidedicatum Martens, 1989 is given.